Modified Hyperbranched Polyglycerol as Dispersant for Size Control and Stabilization of Gold Nanoparticles in Hydrocarbons - Yanyu Shen; Guijin He; Yongsheng Guo; Hujun Xie; Wenjun Fang (Nanoscale Research Letters, 2017)
Abstract Hyperbranched polyglycerol (HPG) is modified with dodecanethiol (DS) via the “thiol−ene” click reaction to obtain an amphiphilic product DSHPG. The molecular structures of DSHPG samples are characterized by NMR, FTIR, and GPC, and the thermal behaviors are characterized by DSC and TGA. Gold nanoparticles (Au NPs) are prepared with DSHPG as the stabilizer and surface-modification reagent. The size of Au NPs can be tuned by changing the molecular weight of HPG. It is observed that the HPG molecular weights of 1123, 3826, and 55,075 lead to the NP diameters of 4.1 nm for Au@DSHPG-1, 9.7 nm for Au@DSHPG-2, and 15.1 nm for Au@DSHPG-3, respectively. The morphology and size of Au NPs are characterized by TEM and DLS. Especially, the dispersion abilities of Au NPs in different pure solvents and co-solvent mixtures are investigated. The long alkyl chains on DSHPG give the ability of Au NPs to be well dispersed in nonpolar solvents. Hydrocarbon-based nanofluids can be obtained from the hydrophobic Au NPs dispersed into a series of hydrocarbons. The dispersion stability for Au NPs in hydrocarbons is monitored by UV-Vis spectroscopy, and the relative concentration of Au NPs is observed to still maintain over 80% after 3600 h.